BS EN 50491-12-2. General requirements for Home and Building Electronic Systems (HBES) and Building Automation and Control Systems (BACS). Part 12-2. Smart grid. Application specification. Interface and framework for customer. Interface between the Home / Building CEM (7th August 2020) - British Standards Institution,
No abstract available